Qualitative Analysis of Drug-Containing Plasma and its Application to Quantitative Analysis and Pharmacokinetic Study of Zexie Decoction Using UPLC-MS/MS - Wu, Jiashuo; Zheng, Shunliang; Zhang, Fangqing; Ruan, Haonan; Xue, Haotian; Wang, Jingxun; Li, Zhuangzhuang; Jin, Weiyi; Wang, Weihua; Xia, Jing; Shi, Yue (Frontiers in Chemistry, 2022)
ZeXie Decoction (ZXD) is one of the traditional Chinese medicine formulas (TCMFs) comprising Alisma orientalis (Sam.) Juzep. (ZX) and Atractylodes macrocephala Koidz. (BZ) in 5:2 ratios and is widely employed in clinical applications since ancient times. In this study, UHPLC-QE-Orbitrap-MS was used for qualitative analysis of ZXD in rats’ plasma after a single oral dose of 750 mg/kg body weight. Afterward, UHPLC-Q-TRAP-MS/MS was used for simultaneous analysis of three bioactive chemical compounds including alisol A, alisol B, and alisol A 24-acetate in ZXD’s ethanol extract. Subsequently, the pharmacokinetic profiles of the three analytes were investigated in rat plasma utilizing UHPLC-Q-TRAP-MS/MS. The multiple reaction monitoring (MRM) mode for the three analytes were at m/z 508.4→383.2 for alisol A, m/z 490.4→365.2 for alisol B, and m/z 550.4→515.5 for alisol A 24-acetate. The analysis method was validated in terms of its accuracy, stability, repeatability, linearity, spiked recovery and matrix effect. As a result, twenty-five chemical constituents of ZXD were putatively identified in plasma, and rapid, sensitive, and accurate methods were established for the quantitative analysis and pharmacokinetic study of ZXD. The findings of this study can provide a scientific base for further study of in vivo pharmacokinetics of TCMFs.